Myomectomy in Two Sisters with Multiple Myomas: A Case Series - Fariba Seyedoshohadaei; Kian Lahourpour; Hana Sohrabi; Seyedeh Tayebeh Ghazavi; Bezad Gholamveisi (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: Uterine myoma is the most common mass in gynecology and affects many women in different societies. Uterine myomas have different types and cause different symptoms that require treatment to prevent further complications. Series: This study reports multiple myomas in two 34-year-old and 31-year-old unmarried sisters. Both patients had severe digestive, urinary and bleeding problems. Due to the fact that the patients were young and childless and wanted to preserve their fertility, they underwent myomectomy by laparotomy. Despite the large number of myomas (56 and 47), in order to preserve fertility, attention was paid to preserving the normal anatomy of the uterus and fallopian tubes, and the uterus was repaired. Conclusion: The presence of multiple myomas in two sisters indicates the great influence of genetics on the incidence of uterine myoma. There are different treatments for these fibroids, one of the most common of which is hysterectomy. However, myomectomy is supported in young and childless patients who wish to preserve fertility despite multiple myomas.